Differentiated Learning Strategies for Children's Religious-Moral Values in the Kurikulum Merdeka - Shalihah, Nisa; Waharjani, Waharjani; Wantini, Wantini (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
The Merdeka Curriculum emphasizes the freedom of students to determine the course of learning according to their interests, needs and potential. However, it should be recognized that each student has a different level of understanding and ability in learning Islam. This study aims to analyze how the application of differentiation learning strategies for children's religious-moral values in the independent curriculum. The research method used is experimental research. The results showed that the results of the T-Test paired sample correlation test using the SPSS application can be concluded that the average post-test score of experimental class students is 30% with a significance value of 0.062, and sig (2 tailed) whose value is smaller than 0.05 which shows that there is a significant difference between pre-test and post-test scores. Differentiated learning enhances early childhood religious values by following this learning model showing significant increases in concept understanding, active participation in learning, and high learning motivation. The differentiated learning model is an effective approach, providing a more relevant and engaging learning experience by accommodating each individual's differences.